7,2 x 13 + 3,6 x 71 + 3,6 + 7,2
= 3,6 x 2 x 13 + 3,6 x 71 + 1,2 x 3 + 7,2
= 3,6 x 26 x 71 + 1,2 x 3 + 7,2
= 3,6 x (26 + 71 + 3)
= 3,6 x 100
= 360
1,2 x 15 + 0,4 x 7 + 1,2 x 16
= 0,4 x 3 x 15 + 04 x 7 + 0,4 x 3 x 16
= 0,4 x 45 + 0,4 x 7 + 0,4 x 48
= 0,4 x (45 + 7 + 48)
= 0,4 x 100
= 40
\(\text{7,2 x 13 + 3,6 x 71 + 3,6 + 7,2 = 3,6 x 2 x 13 + 3,6 x 71 + 1,2 x 3 + 7,2 }\)
\(\text{= 3,6 x 26 x 71 + 1,2 x 3 + 7,2 = 3,6 x (26 + 71 + 3) }\)\(\text{= 3,6 x 100 = 360}\)
\(\text{1,2 x 15 + 0,4 x 7 + 1,2 x 16 = 0,4 x 3 x 15 + 04 x 7 + 0,4 x 3 x 16}\)
\(\text{= 0,4 x 45 + 0,4 x 7 + 0,4 x 48 = 0,4 x (45 + 7 + 48)}\)
\(\text{= 0,4 x 100 = 40}\)